2015
DOI: 10.1186/s13054-015-0904-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of gender to outcome after out-of-hospital cardiac arrest – a report from the International Cardiac Arrest Registry

Abstract: IntroductionPrevious studies have suggested an effect of gender on outcome after out-of-hospital cardiac arrest (OHCA), but the results are conflicting. We aimed to investigate the association of gender to outcome, coronary angiography (CAG) and adverse events in OHCA survivors treated with mild induced hypothermia (MIH).MethodsWe performed a retrospective analysis of prospectively collected data from the International Cardiac Arrest Registry. Adult patients with a non-traumatic OHCA and treated with MIH were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
110
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 39 publications
9
110
3
2
Order By: Relevance
“…This has been associated with the presence of different comorbidities. In men coronary artery disease was observed more frequently, while in women more chronic obstructive pulmonary disease was seen [12]. In our research we found that the occurrence of prehospital ROSC does not depend on gender.…”
Section: Discussionsupporting
confidence: 44%
“…This has been associated with the presence of different comorbidities. In men coronary artery disease was observed more frequently, while in women more chronic obstructive pulmonary disease was seen [12]. In our research we found that the occurrence of prehospital ROSC does not depend on gender.…”
Section: Discussionsupporting
confidence: 44%
“…W badaniu tym po zidentyfikowaniu i uwzględnieniu odmienności w obu grupach płci, płeć żeńska związana była jednak tylko z nieistotną statystycznie poprawą przeżycia NZK [20]. Wyż-szą śmiertelność wśród kobiet obserwowano natomiast w pozaszpitalnym NZK [21].…”
Section: Dyskusjaunclassified
“…In contrast, sex‐related differences in interventions that may highly impact survival, such as bystander or first‐responder resuscitation efforts, are presumably modifiable. Recent European studies found that female sex was associated with lower rates of bystander cardiopulmonary resuscitation (CPR) and early defibrillation, even among witnessed cardiac arrests 2, 5, 12, 13. It is unclear whether such differences also exist in contemporary US cardiac arrest populations.…”
Section: Introductionmentioning
confidence: 99%